درجة توافر القيم التربوية في المنهج المطور لرياض الأطفال فى سورية: دراسة تحليلية - البشلاوي، لوسين محمد; سعد الدين، هبة فيصل; سعد الدين، هبة فيصل (جامعة البعث, 2019)
The research aims to define the degree of existence of educational of educational values in improving course of kindergartens in Syria. And to achieve a purpose of a research, the research depended on the descriptive course and using the list of educational values, prepared by the researcher /fatenbarakatsaleem/ and analysis form of the content and verify the validity and consistency of the analysis the list contains (16) sub-educational values, were classified according to two major fields. The results showed: they are highly available, seven of sub- values in the list of educational values which should be in the improving course of kindergartens. They are: 1- to love, respect and appreciate the parents. 2- generosity and giving .3- friendship 4- to respect the work 5- to commitment to honesty, integrity, loyalty and faith. 6- forgiveness, pardon, compassion and kindness to a medium degree - (8) sub-values are: 1- lore of other people, respect and help them . 2- collective interest 3- lore of altruism 4- adhering to the noble Morality 5- the traffic etiquette 6- to respect elderly and teachers 7- to respect laws , rules and doctrines 8- to respect other people and help them. The values which aren't in the improving course of kindergartens: 1- to respect religion (the faith of man in god is a doctrine and practice. 2- modesty, kindness and politeness. The research suggested the necessity to take care of the kind of the educational values provided to children of kindergarten and the method of providing them, the necessity of considering the properties of developmental of considering the properties of developmental children through the methods to achieve the educational values for them.
يهدف البحث إلى تعرف درجة توافر القيم التربوية في المنهج المطور لرياض الأطفال في سورية ولتحقيق هدف البحث اعتمد البحث على المنهج الوصفي واستخدم قائمة القيم التربوية من إعداد الباحثة فاتن سليم بركات واستمارة تحليل محتوى من إعداد الباحثة وتم التحقق من صدق التحليل وثباته، وتضمنت القائمة (16) قيمة تربوية فرعية تم تصنيفها وفق مجالين رئيسين. وأظهرت النتائج: تتوافر بدرجة مرتفعة (7) من القيم الفرعية الواردة في قائمة القيم التربوية الواجب توافرها في المنهج المطور لرياض الأطفال. وهي 1. محبة الأهل واحترامهم وتقديرهم 2. الكرم والعطاء 3. الصداقة 4. العمل واحترامه 5. الالتزام بالصدق والأمانة والاستقامة والوفاء والإخلاص 6. التسامح والعفو والرحمة والرفق. وبدرجة متوسطة (8) من القيم الفرعية وهي: 1. محبة الناس الآخرين واحترامهم ومساعدتهم 2. المصلحة الجماعية 3. حب الإيثار 4. التمسك بالأخلاق الكريمة 5. آداب السير والتعامل 6. احترام الكبار والمعلمين 7.احترام القوانين والأنظمة والعقائد 8. محبة الناس الآخرين ومساعدتهم والقيم التي لم تتوافر في المنهج المطور لرياض الأطفال هي 1. احترام الدين (إيمان الإنسان بربه عقيدة وممارسة) 2. التواضع واللطافة والتأدب. واقترح البحث ضرورة الاهتمام بنوع القيم التربوية التي تقدم لأطفال الروضة وأساليب تقديمها، وضرورة مراعاة خصائص الأطفال النمائية في أساليب تحقيق القيم التربوية لهم.
Keywords: القيم التربوية -- الأهداف الوجدانية -- المنهج المطور -- رياض الأطفال -- سورية